Efeitos uroprotetores do 2-mercapoetano sulfonato (MESNA), isolado ou associado à dexametasona, na profilaxia da cistite hemorrágica em pacientes submetidos à quimioterapia à base de ifosfamida - Lima, Marcos Venicio Alves (2003)
Based on results obtained in experimental studies, which demonstrated that dexametasone prevenis the development of ifosfamide (IFS) induced hemorrhagic cystitis (HC), a prospective randomized double-blind clinicai study was performed to compare the uroprotective effícacies of the regular 2-mercaptoethananesulfonic acid (MESNA) with MESNA and dexametasone in association in IFS-induced HC. A total of 46 câncer patients being treated at the Institute of Câncer of Ceará Hospital and receiving an ifosfamide- containing chemotherapy program, independent of sex, race, age or clinicai stage were enrolled in this study. They were eligible for participating if the following criteria were fulfilled: ifosfamide dose per day of treatment equal or more than 1.8 g/m2, Kamofsky’s score more than 50; no ifosfamide, cyclophosphamide or glucosteroid therapy in the last four weeks; absence of urinary tract affections or prior pelvic radiation therapy. Eligible patients were randomized into three groups: 1) Those receiving the usual trhee-dose regimen with MESNA. MESNA was given at a dose equal to the ifosfamide dose, divided into three doses: i.v. at the same time (20% of the ifosfamide dose), p.o. at 2 e 6 h following (40% of ifosfamide dose) the ifosfamide treatment. 2) Replacement of the last two dose of MESNA by dexametasone and 3) Addition of dexametasone to the last two dose of MESNA three doses regimen. Cystitis was evaluated by taking into account three parameters: mycroscopic nematuria, cystoscopic aspects and mycroscopic analysis of biopsy specimens. After 24 hour of completion of ifosfamide treatment, urinalysis was performed and hematuria was classified in grades, ranging from I to III, according to the intensity of red blood cells per high-power fíeld. Immediately after this, cystoscopy and mucosal biopsy were performed. Concerning macroscopic evaluation, bladders were examined grossly through cystoscopy, for edema and hemorrhage according to modified Gray's criteria.Three observers performed independent histological examination of biopsy specimens and discussed at the end to confirm the results. Histological aspects were evaluated according to the criteria and scores specially elaborated for this study. A reference group (untreated patients) was used to obtain the baseline scores and the cut off establishment. Statistical significance (p<0.05) was assessed by Fisher’s exact test. According to these parameters, the regular three-dose regimen with MESNA did not provide complete uroprotection although most patients did not have clinicai cystitis develop. Replacement of the two last doses of MESNA by dexametasone conferred similar uroprotection and subclinical cystitis. Finally, the addition of dexametasone to the MESNA three-dose regimen improved MESNA’s uroprotection (p<0.05).